Are physical characteristics different between womens international XV and seven rugby? - Daussin, F. N.; Delforge, E.; Boissière, J.; Joncherey, H.; Vincent, J.; Imbert, S. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Seven rugby and rugby union are team sports characterized by their specific physical requirements. Even if the practice is rugby, it will be useful to identify specific physical profile in order to guide athletes towards a position that will allow them to best use their qualities. Description of performance levels in international womens rugby is very recent and comparison of physical profile between rugby union position and rugby seven has not been done. This study aims to describe anthropometric and physical characteristics of French woman international rugby union and rugby seven players and to determine if there are specific profiles to each position.